2005
DOI: 10.1590/s0102-76382005000300007
|View full text |Cite
|
Sign up to set email alerts
|

A comparação entre o transplante de células tronco mononucleares e mesenquimais no infarto do miocárdio

Abstract: A comparação entre o transplante de células tronco mononucleares e mesenquimais no infarto do miocárdioComparison of mononuclear and mesenchymal stem cell transplantation in myocardium infarction 271 GUARITA-SOUZA, LC ET AL -Comparison of mononuclear and mesenchymal stem cell transplantation in myocardium infarction Braz J Cardiovasc Surg 2005; 20(3): 270-278Resumo Introdução: O transplante de células no miocárdio tem se mostrado tecnicamente reprodutível, entretanto, existem dúvidas em relação a melhor fraçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…The heart is exposed through a left thoracotomy incision and ligation of the proximal coronary artery is performed with 7-0 yarn [13,14]. Thus, it is an experimental model more complex, that beyond the need for thoracotomy is associated with ventilatory support and postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…The heart is exposed through a left thoracotomy incision and ligation of the proximal coronary artery is performed with 7-0 yarn [13,14]. Thus, it is an experimental model more complex, that beyond the need for thoracotomy is associated with ventilatory support and postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…In the control group, as a result of deterioration of ventricular function after AMI, it already was expected that ventricular remodeling would happen. However, the sedentary group with cells showed statistically significant ventricular dilation, which was also identified in a study published by the same group [14]. Regarding the trained group with cells, although ventricular dilation is identified, it was considered that there was stabilization of ventricular remodeling.…”
Section: Discussionmentioning
confidence: 59%
“…It is believed that factors released due to paracrine effect of stem cells can promote reduction of the fibrosis area, suggesting recovery of left ventricular function, which can be corroborated with improved LVEF and limiting ventricular remodeling. These two mechanisms may also be explained by the angiogenic potential of bone marrow mononuclear stem cells, previously described in other studies and the mechanisms of vasodilation produced by physical activity [14,15].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The first study using the mononuclear fraction appeared in cardiology and showed promising results, encouraging the use of these cells as a treatment in other clinical situations (Guarita‐Souza et al, 2005; Martino et al, 2006). Caldas et al (2008 studied the utilization of mononuclear and mesenchymal cells in a renal failure model using Wistar rats.…”
Section: Introductionmentioning
confidence: 99%